(untitled) (International Journal of Latest Technology in Engineering Management & Applied Science, 2026)
This paper examines Pune’s evolving municipal wastewater management framework as a model for sustainable urban development policy in rapidly urbanising Indian cities. Through a comprehensive analysis of infrastructure expansion, technological innovation, and regulatory frameworks, we assess the effectiveness of decentralised treatment strategies in addressing urban environmental challenges. Our study reveals that despite significant infrastructure investments totalling ₹1,173 crore under the JICA-funded Project for Pollution Abatement of River Mula-Mutha (PARMM), Pune continues to face a 503 MLD daily treatment gap, with only 49% of generated sewage receiving treatment. Using a multi-parametric policy assessment, integrating performance data from 11 sewage treatment plants, policy documents, and environmental monitoring reports, the research finds that while technological diversification demonstrates promise, persistent funding delays, land acquisition disputes, and the "subsidy barrier" in water pricing threaten environmental sustainability outcomes. The research contributes to sustainable urban development literature by demonstrating how policy integration, technology choice, institutional coordination, and financial sustainability mechanisms determine wastewater management effectiveness.